GaN/InGaN avalanche phototransistors. (5th February 2015) - Shen, Shyh-Chiang; Kao, Tsung-Ting; Kim, Hee-Jin; Lee, Yi-Che; Kim, Jeomoh; Ji, Mi-Hee; Ryou, Jae-Hyun; Detchprohm, Theeradetch; Dupuis, Russell D.
Abstract: We report on III–nitride (III–N) avalanche phototransistor (APT) action by illuminating ultraviolet (UV) photons onto a GaN/InGaN npn heterojunction bipolar transistor in an open-base configuration. A high responsivity of >1 A/W was measured for the device operating at a collector-to-emitter voltage ( V CE ) of <15 V in the phototransistor mode. The carrier multiplication in the reversed biased collector leads to a photocurrent avalanche as V CE increases. At λ = 380 nm, the GaN/InGaN APT shows a responsivity of >68 A/W at V CE = 95 V. The InGaN APT demonstrates the feasibility of using III–N bipolar transistor structures for high-sensitivity UV photodetection applications.